2022
DOI: 10.1088/1361-6439/ac855a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics of laminated film vibrator using an ultra-thin MEMS actuator

Abstract: This paper describes fabrication of a laminated film vibrator that uses an ultra-thin micro-electric mechanical system (MEMS) and the effect of lamination on the actuator. The thickness of the ultra-thin MEMS actuator fabricated by ultra-thin MEMS technology was 7.26 µm, making it especially flexible. The vibrator was actuated by applying voltage on a lead zirconate titanate (PZT) thin film. Then, we applied a lamination method to package the actuator. However, the lamination structure influenced the mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…A resonant frequency change due to mounting the mechanism and applying load on the vibrator might also enhance vibrotactile intensity at its frequency. Although we confirmed that the vibrators we developed had no resonance within the vibrotactile bandwidth (∼500 Hz), with no load applied to the vibrator [18], it is insightful to measure the resonant frequency with a load considering that the skin is pressed against the vibrator. Therefore, Experiment 1 (Section III-A) measures the displacement frequency response of the vibrator with the lever mechanism and load.…”
Section: Related Workmentioning
confidence: 63%
“…A resonant frequency change due to mounting the mechanism and applying load on the vibrator might also enhance vibrotactile intensity at its frequency. Although we confirmed that the vibrators we developed had no resonance within the vibrotactile bandwidth (∼500 Hz), with no load applied to the vibrator [18], it is insightful to measure the resonant frequency with a load considering that the skin is pressed against the vibrator. Therefore, Experiment 1 (Section III-A) measures the displacement frequency response of the vibrator with the lever mechanism and load.…”
Section: Related Workmentioning
confidence: 63%
“…Since the discovery and synthesis of piezoelectric materials, researchers have gradually realized that piezoelectric technology can be widely used in biomedicine [1][2][3], flexible electronic devices [4,5], flexible generators [6][7][8][9], ultrathin film vibrators [10], piezoelectric photoelectronic solar cells [11,12] and many other fields. Many kinds of piezoelectric materials have been reported to have high piezoelectric properties and high electromechanical coupling, such as epitaxial wurtzite Sc x Al 1-x N ultrathin films [13] and nanocomposite [14,15].…”
Section: Introductionmentioning
confidence: 99%